2015
DOI: 10.1149/2.0831510jes
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Electrospun Photo-Cross-Linkable Polymer Nanofibers Incorporating Multiwall Carbon Nanotubes and Enzyme for Biosensing

Abstract: Herein, we report the easy and rapid fabrication of water-stable electrospun nanofibers from blends of the photochemically crosslinkable polyvinyl alcohol styrylpyridinium polymer (PVA-SbQ), carboxylated multiwall carbon nanotubes (MWCNT-COOHs) and glucose oxidase (GOx) for electrochemical biosensor application. Different electrospinning parameters including flow rate, applied voltage, distance between tip and collector, polymer concentration and MWCNT-COOHs content in the electrospun solution were tailored to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…1). This was mainly due to the fact that the addition of MWCNTs could enhance the conductivity of the spinning solution, resulting in a decrease of the fiber diameter [26,27]. If continuing to increase the MWCNTs dosage to 2.0 wt%, the fibrous diameter became fine, but some beads also appeared in the fibers (Fig.…”
Section: Morphology and Structure Of Electrospun Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This was mainly due to the fact that the addition of MWCNTs could enhance the conductivity of the spinning solution, resulting in a decrease of the fiber diameter [26,27]. If continuing to increase the MWCNTs dosage to 2.0 wt%, the fibrous diameter became fine, but some beads also appeared in the fibers (Fig.…”
Section: Morphology and Structure Of Electrospun Nanofibersmentioning
confidence: 99%
“…Various MWCNTs modified EFMs (MWCNTs-EFMs) have been prepared for the immobilization of enzyme, and many studies have demonstrated that MWCNTs could effectively increase electron transfer between enzymes and membrane electrodes or substrates [23][24][25]. However, most of researchers prepared the MWCNTs-EFMs firstly, and then immobilized enzymes on the surface of membrane by adsorption or crosslinking attachment [23,25,26]; some obtained the MWCNTs modified enzyme-carrying EFMs through co-electrospinning the mixture of the MWCNTs/enzyme/polymer solutions [27]. There are few reports on the preparation of enzyme-carrying EFMs by emulsion electrospinning for improving their performances.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been extensively used to immobilize enzymes [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], antibodies [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], DNA strands [ 71 , 72 , 73 ] and aptamers [ 74 , 75 ]. Another way to proceed, more specifically developed for enzyme biosensors, consists in entrapping the bioactive molecules inside the NFs by electrospinning a blend of enzymes and polymer [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Electrospun Nfs In Biosensorsmentioning
confidence: 99%
“…Figure 5 shows a setup of an electrospinning instrument with a flat stationary collector. The setup consists of a high-voltage supply, polymer solution in a syringe and the collector screen [42].…”
Section: Electrospinning Techniquementioning
confidence: 99%
“…Schematic illustration of electrospinning setup with flat stationery collector. Reproduced with permission from[42].…”
mentioning
confidence: 99%